Social Cultural Engineering and the Singaporean State - Kuah, Khun Eng (Springer Singapore, 2018)
This book, a collection of previously published articles, focuses on the role of the Singaporean State in social cultural engineering. It deals with the relationship between the Singaporean state and local agencies and how the latter negotiated with the state to establish an acceptable framework for social cultural engineering to proceed. The book also highlights the tensions and conflicts that occurred during this process. The various chapters examine how the Singaporean state used polices and regulatory control to conserve and maintain ethno-cultural and ethno-religious landscapes, develop a moral education system and how the treatment of women and its morality came into alignment with the values that the state espoused upon from the 1980s through the 1990s.